Peran Pendampingan terhadap Kompetensi Menulis Artikel Berstandar Jurnal Terakreditasi Sinta - Jumini, Sri; Parmin, P; Putri Hanifah, Desty; Ariyani, Mila; Triyani, Anisa; Jannata, Taufan; Haryanto, Sri (Carmin: Journal of Community Service, 2024)
The rapid development of science and technology requires teachers as education activists to always follow updates in the learning process. Update information is obtained through research. A study requires skills in writing. The purpose of this community service was to determine the role of mentoring in writing articles on teachers' writing competence. The method used is the Participatory Action Research (PAR) approach. Mentoring is carried out online and offline. During online classes, teachers get material from the class created through the WhatsApp Group platform. Writing competence data is taken with comprehension test questions and assessments of articles made by mentoring participants. The test results show that teachers' writing competence shows an average of 67. Intensive mentoring is carried out on articles made by participants so that understanding increases. The impact of mentoring in writing articles, teachers have good writing skills and analyze problems in the classroom that are developed in research to find innovative solutions that can be applied to learning.